The Effect of Applying an Interdisciplinary Approach in the Management of Patients with Temporomandibular Joint (TMJ) Disorders at Dr. M. Djamil General Hospital, Padang, Indonesia - Gunawan, Gunawan; Edi Sahputra (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Temporomandibular joint (TMJ) disorders are a common health problem with significant global prevalence. Effective management of TMJ requires an interdisciplinary approach involving various health professions, such as dentists, physiotherapists, and psychologists. Methods: This study aims to evaluate the effect of applying an interdisciplinary approach in the management of patients with TMJ disorders at Dr. M. Djamil General Hospital, Padang, Indonesia. A retrospective cohort study was conducted on TMJ patients referred to an interdisciplinary team between 2018 - 2023. Patient data was collected from electronic medical records and analyzed to compare the outcomes of patients who received an interdisciplinary approach with those who received a traditional approach. Results: The results showed that the application of an interdisciplinary approach in the management of TMJ patients at Dr. M. Djamil General Hospital, Padang, Indonesia was associated with significant improvements in patient symptoms, including pain, joint dysfunction, and quality of life. Patients who received an interdisciplinary approach also demonstrated higher levels of satisfaction with their care. Conclusion: Implementation of an interdisciplinary approach in the management of TMJ patients at Dr. M. Djamil General Hospital, Padang, Indonesia was associated with significant improvements in patients' symptoms and their level of satisfaction with treatment. This approach is recommended for the management of TMJ patients in all clinical settings.